Risk assessment and ranking of pesticide residues in Chinese pears - Zhi-xia LI; Ji-yun NIE; Zhen YAN; Guo-feng XU; Hai-fei LI; Li-xue KUANG; Li-gang PAN; Han-zhong XIE; Cheng WANG; Chuan-de LIU; Xu-bo ZHAO; Yong-ze GUO (Journal of Integrative Agriculture, 2015)
The presence of pesticide residues in pears is a serious health concern. This study presents the results from a 2-year investigation (2013–2014) that used gas chromatography, GS/MS and UPLC/MS-MS to measure the levels of 104 pesticides in 310 pear samples. In 93.2% of the samples, 43 pesticides were detected, of which the maximum residue levels (MRLs) were exceeded in 2.6% of the samples. Multiple residues (two to eight compounds) were present in 69.7% of the samples; one sample contained nine pesticides and one sample contained 10. Only 6.8% of the samples did not contain residues. To assess the health risks, the pesticide residue data have been combined with daily pear consumption data for children and adult populations. A deterministic model was used to assess the chronic and acute exposures based on the Joint Meeting on Pesticide Residues (JMPR) method. A potential acute risk was demonstrated for children in the case of bifenthrin, which was found to be present at 105.36% of the acute reference dose (ARfD) value. The long-term exposure of the Chinese consumer to pesticide residues through the consumption of raw pears was far below the acceptable daily intake (ADI) criterion. Additionally, the matrix ranking scheme was used to classify risk subgroups of pesticides and pear samples. In general, 95.5% of samples were deemed to be safe and nine pesticides were classified as being of a relatively high risk. The findings indicated that the occurrence of pesticide residues in pears should not be considered a serious public health problem. Nevertheless, a more detailed study is required for vulnerable consumer groups, especially children. Continuous monitoring of pesticides in pears and tighter regulation of pesticide residue standards are recommended.